Últimas investigaciones en tecnología del algodón - Laguna Mauricio, Hilder (2019)
This thesis topic is about latest research in cotton technology, it was considered of great importance in past decades the fine characteristics of its long fibers (tangüis) and extra long (pima) gained great value and prestige in the world however in In recent years, cultivated areas have reduced as well as their production and yield. Due to this problem, domestic demand for cotton fiber has to be covered with imports mostly from the United States of America due to fiber quality and tariff benefits for imports into that country. Taking into account that cotton is an economic and social crop, the present work seeks to analyze the current situation of cotton, through statistical data from MINAGRI and its comparison over the last years. Likewise, to know the commercialization and importation of cotton fiber, with the classification of cottons made by the USDA (Department of Agriculture of the United States), the pricing in contracts of purchase and sale of fiber in Peru for these imports. Likewise, statistical data on the evolution of imports in recent years is shown. On the other hand, a study of the cotton production chain will be carried out. It is expected that the results of the present investigation contribute to broaden the dialogue around the problem of the cotton business in Peru